An experimental and analytical study of the sound wave propagation in beam formed from rubberized concrete material - Mohamed, Salhi; Omar, Safer; Mouloud, Dahmane; Nouria, Hassene Daouadji; Li, Alex; Amar, Benyahia; Toufik, Boubekeur; Abdelhak, Badache (Earthquakes and Structures, 2024)
The amount of wave propagation through a rubber concrete construction is the subject of the current investigation. Rubber tire waste was used to make two different types of cement mixtures. One type contains sand substitute in amounts ranging from 15% to 60% of the total volume, while the other has gravel with diameters of 3/8 and 8/15 and 15% sand in the same mixture. A wide variety of concrete forms and compositions were created, and their viscous and solid state characteristics were assessed, along with their short-, medium-, and long-term strengths. Diffusion, density, mechanical strength resistance to compressive force, and ultrasound wave propagation were also assessed. The water-to-cement ratio and plasticizer were used in this investigation. In the second part of the study, an analytical model is presented that simulates the experimental model in predicting the speed of waves and the frequencies accompanying them for this type of mixture. Higher order shear deformation beam theory for wave propagation in the rubberized concrete beam is developed, considering the bidirectional distribution, which is primarily expressed by the density, the Poisson coefficient, and Young' s modulus. Hamilton's concept is used to determine the governing equations of the wave propagation in the rubberized concrete beam structure. When the analytical and experimental results for rubber concrete beams were compared, the outcomes were very comparable. The addition of rubber gravel and sandy rubber to the mixture both resulted in a discernible drop in velocities and frequencies, according to the data.
Number: 2